ANALISIS GAYA KEPEMIMPINAN TERHADAP TURNOVER INTENTION KARYAWAN PADA RUMAH SAKIT IBU DAN ANAK GEBANG MEDIKA TANGERANG - Lestari, Riska; Handayani, Rima (Journal of Research and Publication Innovation, 2024)
This research is entitled "Analysis of Leadership Style on Employee Turnover Intention at Gebang Medika Tangerang Mother and Child Hospital". The purpose of this research is to determine and analyze the leadership style at the Gebang Medika Tangerang Mother and Child Hospital. In this research, researchers used qualitative methods. This research was carried out using interview techniques, observation, documentation and theoretical studies based on bibliography and other references. Researchers conducted interviews with 6 sources consisting of Medical Services & Support Manager, General Manager, Casemix Coordinator, Environmental Health, Finance and Registration Staff. So, the result of the leadership style applied by the Gebang Medika Tangerang Mother and Child Hospital is to apply an autocratic leadership style. This leadership style has criteria or characteristics that always consider the organization as personal property, are arrogant, identify personal goals with organizational goals, consider subordinates as tools. simply, does not want to accept criticism and suggestions, and is too dependent on power. An autocratic leadership style has a significant effect on employee turnover, because employees feel uncomfortable with the nature of leaders who tend to be moody, cannot control their emotions and do not involve employees when making decisions.